Elevated NCOR1 disrupts a network of dietary-sensing nuclear receptors in bladder cancer cells - Abedin, S. Asad (Oxford University Press, 2009)
Increasingly invasive bladder cancer cells lines displayed insensitivity toward a panel of dietary-derived ligands for members of the nuclear receptor superfamily. Insensitivity was defined through altered gene regulatory actions and cell proliferation and reflected both reduced receptor expression and elevated nuclear receptor corepressor 1 (NCOR1) expression. Stable overexpression of NCOR1 in sensitive cells (RT4) resulted in a panel of clones that recapitulated the resistant phenotype in terms of gene regulatory actions and proliferative responses toward ligand. Similarly, silencing RNA approaches to NCOR1 in resistant cells (EJ28) enhanced ligand gene regulatory and proliferation responses, including those mediated by peroxisome proliferator-activated receptor (PPAR) γ and vitamin D receptor (VDR) receptors. Elevated NCOR1 levels generate an epigenetic lesion to target in resistant cells using the histone deacetylase inhibitor vorinostat, in combination with nuclear receptor ligands. Such treatments revealed strong-additive interactions toward the PPARγ, VDR and Farnesoid X-activated receptors. Genome-wide microarray and microfluidic quantitative real-time, reverse transcription–polymerase chain reaction approaches, following the targeting of NCOR1 activity and expression, revealed the selective capacity of this corepressor to govern common transcriptional events of underlying networks. Combined these findings suggest that NCOR1 is a selective regulator of nuclear receptors, notably PPARγ and VDR, and contributes to their loss of sensitivity. Combinations of epigenetic therapies that target NCOR1 may prove effective, even when receptor expression is reduced.